Effects of new Torulaspora delbrueckii killer yeasts on the must fermentation kinetics and aroma compounds of white table wine - Velázquez, Rocío; Zamora, Emiliano; Álvarez, María L.; Hernández, Luis M.; Ramírez, Manuel (Frontiers in Microbiology, 2015)
Torulaspora delbrueckii is becoming widely recommended for improving some specific characteristics of wines. However, its impact on wine quality is still far from satisfactory at the winery level, mostly because it is easily replaced by S. cerevisiae-like yeasts during must fermentation. New T. delbrueckii killer strains were here isolated and selected for winemaking. They killed S. cerevisiae yeasts and were able to dominate and complete the fermentation of sterile grape must. Sequential yeast inoculation of non-sterile white must with T. delbrueckii followed by S. cerevisiae did not ensure T. delbrueckii dominance or wine quality improvement. Only a single initial must inoculation at high cell concentrations allowed the T. delbrueckii killer strains to dominate and complete the must fermentation to reach above 11% ethanol, but not the non-killer strains. None of the wines underwent malolactic fermentation as long as the must had low turbidity and pH. Although no statistically significant differences were found in the wine quality score, the S. cerevisiae-dominated wines were preferred over the T. delbrueckii-dominated ones because the former had high-intensity fresh fruit aromas while the latter had lower intensity, but nevertheless nice and unusual dried fruit/pastry aromas. Except for ethyl propanoate and 3-ethoxy-1-propanol, which were more abundant in the T. delbrueckii–dominated wines, most of the compounds with fresh fruit odour descriptors, including those with the greatest odour activity values (isoamyl acetate, ethyl hexanoate, and ethyl octanoate), were more abundant in the S. cerevisiae–dominated wines. The low relative concentrations of these fruity compounds made it possible to detect in the T. delbrueckii–dominated wines the low-relative-concentration compounds with dried fruit and pastry odours. An example was γ-ethoxy-butyrolactone which was significantly more abundant in these wines than in those dominated by S. cerevisiae.